Techno-economic analysis and method development applied to an aerobic gas fermentation and supercritical water gasification process - Rodgers, Sarah (2024)
The chemical and fuels industry's reliance on fossil-based feedstocks necessitates a shift to low-emission renewables like agricultural residues, municipal solid wastes, and industrial off-gases. Gas fermentation employs microbes to convert gaseous carbon-rich streams into renewable chemicals. The current state of commercial gas fermentation relies on anaerobic bacteria. However, aerobic bacteria offer the potential to target a broader range of products. Despite this, an inherent disadvantage of aerobic gas fermentation is its poor thermodynamic efficiency. Integrating aerobic gas fermentation with Supercritical Water Gasification (SCWG) addresses this challenge, creating a promising biochemical production platform. The integration utilises the low-temperature fermentation heat to pre-heat biomass for SCWG and reclaims the energy from depressurising the SCWG effluent using a turbo-expander. In addition, a key benefit of SCWG is its ability to exploit wet, low-value wastes. Such feedstocks are abundantly available and have limited resource competition as they are uneconomical to exploit via conventional gasification. Despite these benefits, the economic feasibility needs verifying which includes the selection of optimal feedstocks, feasible production capacities, and geographic considerations to identify promising biorefinery scenarios.